Disenchanting citizenship : Mexican migrants and the boundaries of belonging - Plascencia, Luis F. B. (New Brunswick, N.J. : Rutgers University Press, 2012)
Luis F.B. Plascencia's Disenchanting Citizenship explores two interrelated issues: U.S. citizenship and the Mexican migrants' position in the United States. Through an extensive and multifaceted collection of interviews, ethnographic fieldwork, ethno-historical research, and public policy analysis, Plascencia probes the ways in which citizenship discourses are understood and taken up by individuals. The book uncovers citizenship's root as a Janus-faced construct that encompasses a simultaneous process of inclusion and exclusion. This notion of citizenship is mapped on to t.
Introduction: locating citizenships -- Fields of citizenship -- The Janus face of citizenship: the side of inclusion -- The Janus face of citizenship: the side of exclusion -- The making of citizens: promoting and schooling -- Bearing true faith and allegiance: entering the circle of citizenship -- Desire, sacrifice, and disenchantment -- Epilogue: the boundaries of birth and power.
Includes bibliographical references (pages 225-245) and index.
Print version record.
English.
JSTOR
Keywords: Mexican Americans -- Ethnic identity; Mexican Americans -- Civil rights; Mexican Americans -- Social conditions; Mexicans -- Migrations; Citizenship -- United States; Noncitizens -- United States; United States -- Politics and government; United States -- Ethnic relations; United States -- Emigration and immigration -- Government policy; Américains d'origine mexicaine -- Identité ethnique; Américains d'origine mexicaine -- Droits; Américains d'origine mexicaine -- Conditions sociales; Mexicains -- Migrations; Immigrants clandestins -- États-Unis.; États-Unis -- Politique et gouvernement; États-Unis -- Relations interethniques; États-Unis -- Émigration et immigration -- Politique gouvernementale; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Ethnic Studies -- General; SOCIAL SCIENCE -- Minority Studies; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies; Noncitizens; Citizenship; Emigration and immigration -- Government policy; Ethnic relations; Mexican Americans -- Civil rights; Mexican Americans -- Ethnic identity; Mexican Americans -- Social conditions; Politics and government; United States